IMPLEMENTASI PERATURAN DAERAH KABUPATEN BENGKALIS NOMOR 1 TAHUN 2016 TENTANG KETERTIBAN UMUM (STUDI TAMU WAJIB LAPOR 1X24 JAM DI KELURAHAN GAJAH SAKTI KECAMATAN MANDAU KABUPATEN BENGKALIS TAHUN 2021) - Nadila Azani; Adlin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
With the enactment of the Bengkalis Regency Regional Regulation Number 1 of 2016 concerning Public Order, especially in article 55 concerning guests who must report 1x24 hours, it can prevent or minimize the occurrence of crimes that can harm local residents. Therefore it is important to implement guest regulations that must report 1 x 24 hours in order to maintain the security of the local community to be safe and secure. This study aims to find out whether the Regional Regulation of Bengkalis Regency Number 1 of 2016 concerning Public Order is communicated to the public and to find out how resources, dispositions and bureaucratic structures are in implementing this regional regulation. The research approach used is a qualitative approach. This type of research is descriptive. The location of this research is in Gajah Sakti Village, Mandau District, Bengkalis Regency. Types and sources of research data are divided into primary data and secondary data with data collection techniques through interviews and secondary data in the form of supporting data related to the Regional Regulation of Bengkalis Regency Number 1 of 2016 concerning Public Order. The result of this study is the implementation of Bengkalis Regency Regional Regulation Number 1 of 2016 concerning Public Order concerning guests who are required to report 1x24 hours that in implementing this regional regulation it has been implemented but there are still several indicators that still need to be improved in the resource indicator in the facilities and disposition section. Keywords: Regional Regulation, Communication, Resources, Disposition, Bureaucratic Structure